Development of Interactive E-Books Based on Problem-Based Learning on the Material of the Earth's Surface Layers - Lutfiani, Firda Dian; Andriani, Aldina Eka (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2025)
Limited sources of interactive electronic-based teaching materials can result in low cognitive learning outcomes for students, especially in science learning. This study aims to describe the development design and test the feasibility and effectiveness of Interactive E-Books based on Problem Based Learning in improving science learning outcomes in grade V students of SDN Ngijo 01 Semarang City. This research and development (RnD) study uses the Borg and Gall model. Data collection techniques are tests and non-tests, tests with (pre-test and post-test), and non-tests in the form of observations, interviews, questionnaires, and documentation. Data analysis was carried out using normality tests, t-tests, and N-Gain. The results of the study indicate that the development design of Interactive E-Books based on Problem Based Learning was successfully developed with the Canva and Flipbook applications, its components such as the main page, foreword, advantages of e-books, table of contents, instructions for use, activity instructions, achievement indicators, concept maps, materials based on Problem-Based Learning syntax, interactive learning videos, LKPD, educational games, and developer profiles. The feasibility of the interactive e-book from material and media experts is very feasible, supported by teacher and student assessments, which also show a very feasible category. The novelty of this study lies in the presentation of material that applies the syntax of the Problem-Based Learning model, which includes stimulus variations, grouping, presentation of results, and reflection, as well as the integration of interactive elements such as images, videos, and sounds. There are interactive edugames to facilitate understanding of the concept of the earth's surface layers. The effectiveness of the E-Book is shown by an increase in value of (15.25) supported by the results of the t-test (0.001) and the N-Gain score of (0.50) in the medium category. The research that has been conducted shows that the conclusion of this study shows that the Interactive E-Book based on Problem Based Learning has been successfully developed, is very feasible, and effective in improving the science learning outcomes of grade V students of SD N Ngijo 01 Semarang City on the material of the earth's surface layers.